Parental Bonding And Individual Self-Development: Enhancing The Concept Of Family Education - Prehanto, Adi; Ali, Mohammad; Hernawan, Asep Herry (Universitas Ahmad Dahlan, 2023)
In the current era, education remains an integral part of life, crucial for enhancing human resources. Schools are traditionally seen as central to developing children's competencies. However, this study seeks to examine the role of family as a provider of comprehensive and holistic education, specifically in the context of orphanages. The study aimed to explore the impact of family education on the moral and character development of orphans. A mixed-method design, particularly a sequential explanatory design, was employed in this research. The study involved 34 respondents, including children from orphanages and orphanage caregivers, selected through purposive sampling. Data collection included a literature review of relevant journals and parental bonding questionnaires. The analysis utilized a mixed method approach, with qualitative analysis conducted first, followed by quantitative analysis. The results indicated that family education, especially parental bonding, significantly influences the improvement of children's moral and character development. The study implies that family education extends beyond assisting children at home and enrolling them in higher education; it also encompasses advising, building trust, and serving as positive role models.